STUDY OF FACTORS INFLUENCING YOUNG DRIVERS’ BEHAVIOR IN PALANGKA RAYA CITY - Maria Lestari Manik (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2026)
This study aims to analyze the factors influencing young drivers’ behavior in Palangka Raya. Young drivers are considered a vulnerable group in traffic due to limited driving experience, emotional instability, and insufficient understanding of traffic regulations, which may lead to risky driving behavior. This research adopts the Theory of Planned Behavior (TPB) framework, focusing on knowledge, attitude, subjective norms, and perceived behavioral control as the main influencing factors.The study employed a quantitative descriptive approach using a survey method. Data were collected through questionnaires distributed to 100 young drivers aged 15– 24 years. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. Instrument validity and reliability tests, as well as classical assumption tests, were conducted to ensure data accuracy. The results indicate that knowledge, attitude, and perceived behavioral control have a significant positive effect on young drivers’ behavior, while subjective norms do not have a significant effect. Simultaneously, all independent variables significantly influence young drivers’ behavior. These findings suggest that improving young drivers’ behavior requires enhancing traffic safety knowledge, fostering positive attitudes toward safe driving, and strengthening self-control while driving.